(untitled) (Research, Society and Development, 2021)
The physicochemical characterization of AC in the elimination of DEP in synthetic effluent was studied. Through the adsorption kinetics and isotherms, according to the factorial design of 11 tests and mathematical models, the influence of temperature, pH, and CA mass was verified. AC presented low surface area (554.228 m2 g-1), microporous area (460.0539 m2 g-1) and high microporous volume (0.253081 cm3 g-1) by the BET and BJH method, and due to activation, high basicity, pHPZC (7.2). Elemental and surface group analysis by the Boehm method revealed a predominance of basic groups (0.845 meq g-1), lactones (0.211 meq g-1) and phenols (0.169 meq g-1), confirmed by infrared spectroscopy (FTIR ) by the presence of quinone, lactone and carbonyl groups. The adsorption treatment presented higher coefficients of determination (R2 > 0.90) in the study of kinetics for the pseudo-second order model, and of isotherms for the Freundlinch model. AC presented an 83.5% DEP elimination rate, a DEP adsorption capacity of 27.006 mg g-1 at pH 7, with 0.4 g of AC at 30ºC in 360 minutes, however, it reduced by 13% its rate and 20.598 mg g-1 of adsorption capacity at pH 11, with 0.2 g of AC at 15ºC in 360 minutes. For the adsorption capacity and DEP elimination rate there was no significant difference in treatments with (p < 0.5). In the Thermogravimetric Analysis (TGA), the decomposition close to 600ºC, and by Scanning Electron Microscopy (SEM), the textural properties were maintained.